Primary obstetric ultrasound : comparing a detail ultrasound only protocol with a booking ultrasound protocol - Poggenpoel, Elizabeth J. (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MMed (Obstetrics and Gynaecology))--University of Stellenbosch, 2010.